Projectmanagement for dummies - Graham, Nick, ....-; Portny, Stan, ....- (Chichester : John Wiley & Sons, 2015)
Get projects done on time, on budget, and with maximum efficiency In today's time-pressured and cost-conscious global business environment, reliable project management and competent delivery are more important than ever. Increasingly, project management is being seen as an essential management skill for all, as well as a career choice for many. This new UK edition of Project Management For Dummies quickly introduces you to the principles of successful project management with a clear and logical approach to help you deliver your projects, not only successfully, but also more easily. Unique to the UK edition, you'll find clear guidance on using the highly logical product-based approach to project planning, along with advice on how to release the great power of the technique, not only for effective planning, but also for project control. Updated with fresh content, tips, and tactics that cover everything you need to know from a project's start to finish, this accessible guide takes you through every stage of project management. You'll discover how to make project planning easier and more effective, manage resources and stay on track within a budget. Then you'll find help and advice to help you motivate and manage your teams to help them perform at their best. To help you stay at the leading edge, you'll also find two new chapters in this edition explaining project governance and the increasingly important international standard ISO 21500. In short, this book will help you master a highly valuable skill for advancing your career.
Keywords: Projectmanagement